ANALISIS CRYPTOCURRENCY SEBAGAI ALAT ALTERNATIF BERINVESTASI DI INDONESIA - Dinda Anisa; Tuti Anggraini; Khairina Tambunan (Politeknik Ganesha Medan, 2023)
This research was carried out in order to gain a better understanding of cryptocurrencies, as well as the position of Islamic law in relation to them as a form of alternative investment in Indonesia. This research is a qualitative investigation utilizing phenomenological and descriptive methodologies. The data that was used came from the library and was backed by a number of papers and books that were linked to the issues that were investigated in this study using a syar'i normative methodology. It is possible to invest in Crytocurrency, trade Crytocurrency, or utilize Crytocurrency as a form of payment. In addition to Bitcoin, several other forms of Crytocurrency are also seeing widespread use. Different points of view on Crytocurrency can be found within the community, which can give rise to both pros and negatives. Because there is no legislation in Indonesia that recognizes Crytocurrency as a form of payment or currency, it is illegal to utilize Crytocurrency there. Since the price is still volatile and there are still flaws in the security, the discussion around cryptocurrencies such as Bitcoin has not yet reached an advantageous point. Some Ulama say, from the perspective of Islamic law, that this kind of digital currency does not have clarity and cannot be physically seen, allowing for the possibility of fraud. As a result, they consider Crytocurrency to have aspects of Gharar. The usage of Crytocurrency in investment and trading makes it inseparable from speculation about the price, which is highly volatile and is solely used as a tool for making profits and losses. Maysir is a component of Crytocurrency. Because the significance of this crypto currency spans such a wide range of areas, particularly those pertaining to technology and the economy.